Want this question answered?
Be notified when an answer is posted
The standard equation of a circle, with center in (a,b) and radius r, is: (x-a)2 + (y-b)2 = r2
(x - A)2 + (y - B)2 = R2 The center of the circle is the point (A, B) . The circle's radius is ' R '.
Well, honey, the center of that circle is simply the point (3, 9). You see, the equation you provided is in the form (x - h)² + (y - k)² = r², where (h, k) is the center of the circle. So, in this case, the center is at (3, 9). That's all there is to it, sugar.
depends on the equation.
(x - h)2 + (y - v)2 = r2
The standard equation of a circle, with center in (a,b) and radius r, is: (x-a)2 + (y-b)2 = r2
9
(x - A)2 + (y - B)2 = R2 The center of the circle is the point (A, B) . The circle's radius is ' R '.
Well, honey, the center of that circle is simply the point (3, 9). You see, the equation you provided is in the form (x - h)² + (y - k)² = r², where (h, k) is the center of the circle. So, in this case, the center is at (3, 9). That's all there is to it, sugar.
Equation of any circle, with any radius, and its center at any point: [ x - (x-coordinate of the center) ]2 + [ y - (y-coordinate of the center) ]2 = (radius of the circle)2
32+62=45 so the standard form is x2+y2=45
(x - h)2 + (y - k)2 = r2 where h is the x coordinate of the center of the circle. where k is the y coordinate of the center of the circle. where x is the x coordinate of point (x,y) on the edge of the circle. where y is the y coordinate of point (x,y) on the edge of the circle. Additional assistance here: http://www.mathwarehouse.com/geometry/circle/equation-of-a-circle.php
depends on the equation.
You should increase the radius in the standard equation of a circle centered at the origin. The general form is ( x^2 + y^2 = r^2 ), where ( r ) is the radius. By increasing ( r ), you extend the distance from the center to any point on the circle, making it larger.
The general equation of a circle is given by the formula(x - h)2 + (x - k)2 = r2, where (h, k) is the center of the circle, and r its radius.Since the center of the circle is (0, 0), the equation reduces tox2 + y2 = r2So that the equation of our circle is x2 + y2 = 36.
(x-2)^2 +(y-3)^2 = 16
(x - h)2 + (y - v)2 = r2